Growth through ethical role identity work: the case of ethics and compliance officers - Nieuwenboer, Niki A. den (Journal of business ethics, 2025)
Ethics and compliance officers (ECOs) are organizational agents who are responsible for ensuring employees’ ethical and legally compliant behavior. In their ethical organizational roles, ECOs impose ethical expectations on others. In our study, we find that doing so provokes a challenging interpersonal dual threat dynamic where ECOs are perceived as threatening and feel threatened in return, which is a dynamic that ECOs must navigate to be successful. To better understand how ECOs navigate this dynamic, we explore the ethical role identity work that ECOs engage in and demonstrate how ECOs make sense of and respond to the threat dynamic that occurs as they enact their roles. We found two types of identity work: (1) tensions that pull role incumbents toward personalized or impersonalized approaches in their interactions with others and (2) tactics that address the threats and tensions. We also find that ECOs’ identity work facilitates ethical and identity growth for the role incumbent. To make these contributions, we employ grounded theory methods and draw primarily upon a rich qualitative dataset of interviews with ethics and compliance officers. The model we derived from our research contributes to the behavioral ethics literature by illustrating the challenges yet growth possible in enacting ethical organizational roles.